Implementation of noise management in construction site - Nawi, Nur Muizzah (2013)
Recently, safety and health in construction industry are widely being discussed between academics and professionals. It is true that the construction industry is one of the riskiest sectors which contribute to a quite a number of accidents. Noise exposure is one of the hazards in construction site that could lead to accidents and also negative impacts to human health. There are several regulations and guidelines to prevent the massive exposure to construction workers. However, most of the construction workers are lack of awareness about the impacts of the noise emission to their health. The aim of this research is to investigate the current implementation of noise management for a construction site and the perception of the construction workers in the Malaysian construction industry about the hazard of noise. EMP and EMR report was used to investigate the implementation of noise control management in the construction site. Dosimeter was used to measure the noise exposure level for the 1 hour work duration and perception on noise exposure regulations by workers was surveyed by interview. The data on noise exposure was compared with the limits specified by the 3 regulations. The results showed that management team has taken minimum administrative and engineering control related to noise management in construction site. It also found that workers who handles heavy machineries was exposed to high noise level due to noises emit by the machine itself. Unfortunately the construction workers still lack of awareness about the hazards of noise because they do not apply proper PPE during handling the works even though they knew noise is a general problem